Cooperation between Parents and Teachers in Supporting the Development of Social Interaction in Autistic Children: A Case Study of Students at HKBP Tomuan Private Elementary School - Karina Kezia Br Manurung; Natalina Purba; Yanti Arasi Sidabutar (International Journal of Technology and Education Research, 2026)
This study aims to describe the collaboration between parents and teachers in supporting the development of social interactions in autistic children in student F at HKBP Tomuan Private Elementary School. This study uses a qualitative approach with a case study method. The subject in this study is a mild autistic student with the initials F who is in grade VI. Informants in this study consisted of F's parents, homeroom teachers, and teachers closest to student F. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis used the Lexy J. Moleong model through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the development of F's social interactions has changed gradually towards the better. This can be seen from F's ability to begin to respond to communication, be involved in several school activities, and begin to show acceptance of interactions with the surrounding environment. The pattern of assistance provided by parents is carried out through consistent communication, continuous attention, and an approach that adapts to the child's emotional condition. Meanwhile, teachers provide assistance through an individual approach, building emotional comfort, and involving F in social activities in the school environment. Collaboration between parents and teachers is fostered through open communication, shared involvement in understanding the child's needs, and alignment of support patterns between home and school. This collaboration positively influences the development of F's social interactions.